Rasio Mean Platelet Volume (MPV) terhadap hitung trombosit dan Interleukin-6 (IL-6) sebagai prediktor awal kematian pada sepsis neonatal di RSUP Sanglah, Bali, Indonesia - I Putu Sidhi Rastu Karyana; Ni Nyoman Mahartini; I Made Kardana (Intisari Sains Medis, 2020)
Background: Neonatal sepsis is a clinical syndrome in infants aged less than 28 days that arises from a systemic inflammatory response (SIRS) by various infectious causes. Both Interleukin-6 (IL-6) and Mean Platelet Volume (MPV) levels are known to play an important role in worsening neonatal sepsis. This study aims to determine the relationship between MPV ratio to platelet count and IL-6 as an early predictor of death in neonatal sepsis at Sanglah General Hospital, Bali, Indonesia.Methods: This prospective observational cohort study was conducted from November 2019 to February 2020 at Sanglah General Hospital Denpasar, involving 54 pediatric patients diagnosed with neonatal sepsis for less than 28 days. The research samples were collected consecutively. Statistical analysis is the survival analysis, Receiver Operating Characteristic (ROC) curve, linear regression, and Fisher exact test using SPSS software version 20 for Windows.Results: Most of the respondents had an average age of 3.46 ± 7,065 days, followed by male gender (72.22%), SNAD type of sepsis (88.89%), birth weight 2,126.6 ± 794.1 grams, normal birth weight (38.89%), and premature birth (61.11%). The mean MPV level in all subjects was 7.11 ± 1.85 fL, followed by a platelet count (218.511 ± 121.085) cells / µL, MPV / PLT ratio (5.404 ± 5.351), IL-6 levels (215.32 ± 444, 48 pg / mL), and as much as 12.95% died within 28 days of treatment. The results of the survival analysis showed a significant relationship between the MPV value (Cut-off: 6.745 (AUC: 0.650: HR: 4.353; p = 0.033) and the MPV / PLT ratio (Cut-off: 3.73; AUC: 0.690; HR: 4.535; p = 0.033) as an early predictor of mortality in neonatal sepsis at Sanglah General Hospital, Bali, Indonesia.Conclusion: MPV / PLT and MPV ratios can be used as predictors of early mortality within 28 days in patients with clinical neonatal sepsis at Sanglah General Hospital, Bali, Indonesia. Latar Belakang: Sepsis neonatal adalah sindrom klinis pada bayi berumur kurang dari 28 hari yang timbul akibat respon inflamasi sistemik (SIRS) oleh berbagai penyebab infeksi. Kadar Interleukin-6 (IL-6) maupun Mean Platelet Volume (MPV) diketahui berperan penting terhadap perburukan pada sepsis neonatal. Penelitian ini bertujuan untuk mengetahui  hubungan rasio MPV terhadap hitung trombosit maupun IL-6 sebagai prediktor awal kematian pada sepsis neonatal di RSUP Sanglah, Bali, Indonesia.Metode: Penelitian Kohort prospektif observasional dilakukan sejak November 2019 sampai Februari 2020 di RSUP Sanglah Denpasar dengan melibatkan 54 pasien anak yang terdiagnosis sepsis neonatal kurang dari 28 hari. Sampel penelitian dikumpulkan secara konsekutif. Analsis statistik yaitu dengan analisis kesintasan, kurva Receiver Operating Characteristic (ROC), regresi linier, dan tes Fisher exact menggunakan piranti lunak SPSS versi 20 untuk Windows..Hasil: Sebagian besar responden rata-rata berusia 3.46±7.065 hari, diikuti dengan jenis kelamin laki-laki (72,22%), jenis sepsis tipe SNAD (88,89%), berat lahir 2.126,6±794,1 gram, berat badan lahir normal (38,89%), dan lahir prematur (61,11%). Rerata kada MPV pada seluruh subjek adalah 7,11±1,85 fL, diikuti dengan hitung trombosit (218.511±121.085) sel/µL, rasio MPV/PLT (5,404±5,351), kadar IL-6 (215,32±444,48 pg/mL), dan sebanyak 12,95% meninggal dalam 28 hari perawatan.  Hasil analisis kesintasan menunjukkan hubungan bermakna antara nilai MPV (Cut-off: 6,745 (AUC: 0,650: HR: 4,353; p=0,033) dan rasio MPV/PLT (Cut-off: 3,73; AUC: 0,690; HR: 4,535; p=0,033) sebagai prediktor awal kematian pada sepsis neonatal di RSUP Sanglah, Bali, Indonesia.Kesimpulan: Rasio MPV/PLT dan MPV dapat digunakan sebagai prediktor awal kematian dalam 28 hari pada pasien dengan klinis sepsis neonatal di RSUP Sanglah, Bali, Indonesia